Morphological study of sex organs and pollen grain of chosen wild species from Solanaceae family in Iraq (Baghdad Science Journal, 2025)
In this study four species from Solanaceae family was conducted. These four species belong to four different genera (Solanum L. ? Physalis L. ?Withania Pauq. ? Lycium L.)The study included morphological characters of sex organs and their pollen grains for these Iraqi wild plants.The results showed that the position of epipetalous stamens , the shape of anther, their dimensions ,and the length of filaments are important taxonomical characters .On the others hand the shape of their ovaries and stigmas are also important characters in distinguish between these four species .Pollen grains are similar in their general shapes and polarities, they have three germinal furrows and germinal apertures, so they are minor in distinguish between these four species.